Case Report: A Novel Missense Mutation c.517G>C in the UMPS Gene Associated With Mild Orotic Aciduria - Ma, Rui; Ye, Jing; Han, Jiaqi; Gao, Lehong; Wang, Chaodong; Wang, Yuping (Frontiers in Neurology, 2022)
Background Hereditary orotic aciduria (HOA) is a rare genetic disorder of pyrimidine metabolism caused by variations in the uridine monophosphate synthetase (UMPS) gene and inheritance is autosomal recessive. Heterozygous UMPS mutations can also lead to orotic aciduria without clinical consequence. Methods We conducted molecular genetic analyses on proband using whole exome sequencing (WES) and 12 family members using Sanger sequencing for UMPS mutation. We analyzed the urine metabolites of family members carrying UMPS heterozygous variant with standard gas chromatography-mass spectrometry (GC-MS). Results We identified a novel UMPS mutation (c.517G>C) in a Chinese-origin orotic aciduria pedigree. The proband presented with epilepsy and intellectual disability (ID). Other mutation carriers in our pedigree presented with mild orotic aciduria without relevant medical complaints except for the proband. Conclusion Our study further expanded the genotype of orotic aciduria and highlighted the probability of misdiagnosis in clinical practice.